Affective temperaments and personality traits in couple well-being - Carmela Mento; Chiara La Barbiera; Maria Catena Silvestri; Maria Rosaria Anna Muscatello; Clemente Cedro; Antonio Bruno; Gianluca Pandolfo; Fiammetta Iannuzzo; Clara Lombardo (Journal of Mind and Medical Sciences)
Background. The objective of this study is to establish the link between affective temperament traits and maladaptive personality traits, to verify whether the potential presence of elements related to emotional, affective and dysfunctional relational functioning can affect the couple satisfaction, modifying the well-being or discomfort condition. Materials and Methods. A data collection questionnaire was developed to investigate the factors associated with dysfunctional emotional, affective, and relational modes of functioning. The sample consisted of 473 subjects. Data were collected including the TEMPS-A questionnaire, The Dirty Dozen Italian Assessment and the Relationship Assessment Scale (RAS). Results. The findings of this study showed that the subscales of affective temperament were predictors of dark triad traits. The expressive, irritable and hyperthymic temperamental traits were found to be predictors of trait psychopathy; hyperthymic temperament is also a predictor of narcissistic traits and cyclothymic temperament is a predictor of lower couple satisfaction; men show higher scores than women in Dark triad. Conclusions. This study confirmed that temperamental traits can predict maladaptive personality traits belonging to the dark triad and confirms the importance of evaluating maladaptive personality traits to prevent forms of psychological violence in couple.